2004
DOI: 10.1590/s0100-879x2004000600014
|View full text |Cite
|
Sign up to set email alerts
|

Topographic aspects of photic driving in the electroencephalogram of children and adolescents

Abstract: The electroencephalogram amplitude spectra at 11 fixed frequencies of intermittent photic stimulation of 3 to 24 Hz were combined into driving "profiles" for 14 scalp points in 8 male and 7 female normal subjects aged 9 to 17 years. The driving response varied over frequency and was detected in 70 to 100% of cases in the occipital areas (maximum) and in 27 to 77% of cases in the frontal areas (minimum) using as a criterion peak amplitude 20% higher than those of the neighbors. Each subject responded, on averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…In these areas, the reaction peak amplitudes are lower and decrease towards the frontal region. This trend was observed in all other subjects and patients studied (Lazarev et al, 2004). Individual topography of driving peaks' occurrence was very variable across both groups, however, a reduced number of driving responses in the right hemisphere in Fig.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…In these areas, the reaction peak amplitudes are lower and decrease towards the frontal region. This trend was observed in all other subjects and patients studied (Lazarev et al, 2004). Individual topography of driving peaks' occurrence was very variable across both groups, however, a reduced number of driving responses in the right hemisphere in Fig.…”
Section: Resultssupporting
confidence: 58%
“…In computer simulation, this level of prevalence gave a false-positive rate of less than 5% when the spectrum of signals was white, i.e., when there was no response to the stimuli (Lazarev et al, 2001). Our previous research in normal subjects has shown that most of the driving responses detected by this criterion proved to be significant (in relation to the previous background) according to the statistical estimation by spectral F-test (Lazarev et al, 2004).…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…It can be applied either to investigate two diff e rent spectral estimates over the same frequency band or to test samples from the same spectral density over two diff e rent fre q u e n c y b a n d s 8 . On this basis, SFT was applied to the EEG during IPS and showed to be sensitive in detecting spectral changes related to the stimulation 4 . SFT allows a s c e rtaining whether photic driving occurs according to statistical criteria.…”
mentioning
confidence: 99%